O Plano de Ações Articuladas (PAR) como instrumento de organização do Sistema Nacional de Educação: estudo de caso dos municípios de Cariacica e de Vitória/ES - Oliveira, Elisangela dos Santos de (1997)
The object of this research is the analysis of deployment / implementation of the Articulated Actions Plan (PAR), created by the Federal Government through the Commitment All for Education Goal Plan (Decree n. 6.094/2007), and its potential as instrument for organizing the National Education System. The research has the overall objective to analyze the process of deployment / implementation of PAR in two municipalities of Espírito Santo (Cariacica and Vitória) in order to understand how was PAR planning at the national level and at the municipal level; analyze how it was prepared, how it is being implemented and what are the main actions of PAR developed in the municipalities surveyed, identifying the existing articulations between municipalities, states and federal government through the implementation of PAR. The central argument is that PAR is an instrument of central planning, whose implementation requires decentralized actions. Starting by the hypothesis that the organization of municipalities, economically and politically, has implications for the implementation of an educational plan even though it has the same format and standard for the entire country. That is, the political, economic and cultural characteristics of municipality constitute different realities in the implementation of educational policies, which brings an inequality in the provision of quality educational services among federal entities. The research has a qualitative character of the study of case, particularly the study of multicase that according to Triviños (1987), allows the researcher to study two or more individuals or organizations without the need to be limited to the comparative nature factors. As a research problem, the following question is raised: Can the PAR, with its characteristics of centralization / decentralization, contribute to the organization of the National Education System? Research has shown that the implementation of education policy, such as PAR, involves technical, organizational capacity and institutional aspects of the municipalities. In this sense, for the consolidation of the National System of Education, it is necessary that the PAR is not only a political fundraising, but that municipalities have a guiding plan as a catalyst of a State policy.